Individual heart rate variability responses to preseason training in high level female soccer players - Flatt, A. A.; Esco, M. R.; Nakamura, F. Y. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to track changes in training load (TL) and recovery status indicators throughout a 2-week preseason and to interpret the meaning of these changes on an individual basis among 8 division-1 female soccer players. Weekly averages for heart rate variability (logarithm of the root mean square of successive R-R interval differences [lnRMSSD]), TL, and psychometrics were compared with effect sizes (ESs) and magnitude-based inferences. Relationships were determined with Pearson correlations. Group analysis showed a very likely moderate decrease for total TL (TTL) (TTL week 1 = 1,203 ± 198, TTL week 2 = 977 ± 288; proportion = 1/2/97, ES = -0.93) and a likely small increase in lnRMSSD (week 1 = 74.2 ± 11.1, week 2 = 78.1 ± 10.5; proportion = 81/14/5, ES = 0.35). Fatigue demonstrated a very likely small improvement (week 1 = 5.03 ± 1.09, week 2 = 5.51 ± 1.00; proportion = 95/4/1; ES = 0.45), whereas the other psychometrics did not substantially change. A very large correlation was found between changes in TL and lnRMSSD (r = -0.85), whereas large correlations were found between lnRMSSD and perceived fatigue (r = 0.56) and soreness (r = 0.54). Individual analysis suggests that 2 subjects may benefit from decreased TL, 2 subjects may benefit from increased TL, and 4 subjects may require no intervention based on their psychometric and lnRMSSD responses to the TL. Individual weekly changes in lnRMSSD varied among subjects and related strongly with individual changes in TL. Training intervention based on lnRMSSD and wellness responses may be useful for preventing the accumulation of fatigue in female soccer players.